2018
DOI: 10.1111/icad.12335
|View full text |Cite
|
Sign up to set email alerts
|

The presence of high numbers of empty shells in anthropogenic habitats is insufficient to attract shell adopters among the insects

Abstract: Terrestrial snail shells can be considered partial resources for insects, and as such, the expansion of numerous snail species to anthropogenic habitats makes them increasingly available. Here, we address for the first time a complete profile of insects that use empty terrestrial snail shells during the winter period in Central Europe. The specialisation for shells made by certain snail species was uncommon; however, a number of species showed significant preferences for certain shell types. We found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Sapyga quinquepunctata is an unspecialized cleptoparasite in nests of several Megachilidae (Stöckhert 1933;Vicens et al 1993;Vicens et al 1994;Gusenleitner and Gusenleitner 1994;Osorio et al 2018;Müller et al 2018;Torné-Noguera et al 2020). Although it has been reared from nests of Osmia bicolor (Westrich 2018;Heneberg et al 2020), it does not appear to be common in nests of shell-nesting species (Bogusch et al 2019;Heneberg et al 2020). Our findings of S. quinquepunctata and Anthrax aethiops in nests of O. ferruginea represent the first records of nest parasitism in this species.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Sapyga quinquepunctata is an unspecialized cleptoparasite in nests of several Megachilidae (Stöckhert 1933;Vicens et al 1993;Vicens et al 1994;Gusenleitner and Gusenleitner 1994;Osorio et al 2018;Müller et al 2018;Torné-Noguera et al 2020). Although it has been reared from nests of Osmia bicolor (Westrich 2018;Heneberg et al 2020), it does not appear to be common in nests of shell-nesting species (Bogusch et al 2019;Heneberg et al 2020). Our findings of S. quinquepunctata and Anthrax aethiops in nests of O. ferruginea represent the first records of nest parasitism in this species.…”
Section: Discussionmentioning
confidence: 63%
“…Several species display a series of behaviours related to the manipulation, translocation, and camouflaging of the nest shells (Bellmann 1981;Müller et al 2018). Various species of Chrysura golden wasps have been reported as parasitoids of these species (Müller 1994;Westrich 2018;Bogusch et al 2019). However, the nesting biologies of species occurring only in southern Europe remain poorly known (Müller et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies are needed, especially for the species R. infuscatum, which is the rarest of the four species studied (Kasparek 2019). R. sticticum and R. septemdentatum are common species that form large local populations in southern Europe (Torné-Noguera et al 2014;Romero et al 2020) and the latter occurs in steppe habitats of conservation interest in central Europe (Bogusch et al 2019(Bogusch et al , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Myrmecophilous groups such as beetles and butter ies have received special attention, being described in extensive studies (Fiedler 1991 Interactions between gastropods and ant colonies vary according to the species involved, gastropod size, and recognition/camou age strategies (Witte et al 2002;Eguchi et al 2005). The use of shells for nest building has been reported in natural and anthropized environments in several Myrmicinae species, such as Myrmica sabuleti (Meinert, 1860), Temnothorax crassispinus (Latreille, 1798), Temnothorax nigrips (Mayr, 1855), and Temnothorax parvulus (Schenck, 1852) (Bogusch et al 2018). As for the second type of interaction which is documented for Myrmicinae too, studies analyzing nests of the genus Messor in Turkey and Spain found evidence of predation on Eupulmonata shells (Bertrand 2010; Páll-Gergely and Sólymos 2009).…”
Section: Introductionmentioning
confidence: 99%